Foodstuffs. Detection of food allergens by molecular biological methods. Mustard (Sinapis alba) and soya (Glycine max). Qualitative detection of a specific DNA sequence in cooked sausages by real-time PCR Part 5, (16th May 2023) - British Standards Institution,
No abstract available